Pelvic Lymph Node Dissection During Cystectomy for Patients With Bladder Carcinoma With Variant Histology: Does Histologic Type Matter? - Guo, Lijuan; Zhang, Lianghao; Wang, Jiange; Zhang, Xuepei; Zhu, Zhaowei (Frontiers in Oncology, 2020)
Purpose: Adding pelvic lymph node dissection (PLND) to cystectomy offers significant survival benefit. However, it remains unclear whether this benefit persists in all histologic types. The aim of the study was to examine the impact of PLND on overall survival (OS) after cystectomy in bladder carcinoma patients with histological variants. Methods: Within the Surveillance, Epidemiology and End Results database, we identified 16,880 bladder carcinoma patients receiving cystectomy between 2004 and 2015. Patients were stratified according to the following histologic types: transitional cell carcinoma, squamous cell carcinoma, adenocarcinoma, small cell carcinoma, neuroendocrine carcinoma, signet ring cell carcinoma, pseudosarcomatous carcinoma, and other histology. Cox regression models were used to evaluate the effect of PLND on OS stratified by histologic type. Results: Histologic types were significantly associated with the presence of lymph node metastasis in patients with bladder carcinoma (p < .001). In multivariable Cox regression analyses, PLND compared with non-PLND was associated with OS benefit in patients with transitional cell carcinoma (hazard ratio [HR], 0.595; 95% confidence interval [95% CI], 0.557-0.634 [P < .001]), squamous cell carcinoma (HR, 0. 646; 95% CI, 0.494-0.846 [P = .002]), and signet ring cell carcinoma (HR, 0.233; 95% CI, 0.107-0.504 [P < .001]), whereas no significant differences in OS were observed in other histological subsets. Discussion: Our analyses revealed a significant OS benefit from PLND in patients with transitional cell carcinoma, squamous cell carcinoma, and signet ring cell carcinoma. However, a survival benefit of PLND in patients with other histologic types was not demonstrated.